Physical education: taking into account the psycho-emotional state of students - Fedorova M.Yu. ,; Gilfanova E.K. ,; Slonich E.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to justification for the application of techniques and strategies for managing students' emotional well-being in the context of physical education instruction. Methods and structure of the study. A teaching experiment was carried out with a group of second-year male students (n=40) from the Mining Faculty of the Trans-Baikal State University. To enhance the physical fitness of students, a model for the modular planning of physical education classes was created, incorporating techniques and methods for regulating the emotional state. Results and conclusions. The simulation of the educational process through the implementation of specific exercises designed to enhance and cultivate psychophysical attributes and the body's inherent adaptive capacities has proven to be a successful strategy for optimizing the physical education experience. This approach has also had a positive impact on the students' psychological well-being. The study's findings indicate a positive trend in the students' psychological state, cognitive abilities, and psychomotor skills.